(untitled) (Revista de Ciências Agroveterinárias, 2023)
Depth dimensions are a fundamental linear type trait in the animal body included in dairy cattle science. Unfortunately, the prominent body depth dimension to milk yield is unspecified in lucidity. Thus, the objective of the current research was to identify the excellent body depth dimension of dairy cattle for milk yield as a selection precedence trait. The experiment employed 121 lactation Holstein cows aged specify as 2–6, raised on an Indonesian smallholder commercial dairy farm. R version 4.2.1 with RStudio software simultaneously worked as a statistical analysis tool. The principal component analysis (PCA), correlation, and regression analyses were executed sequentially. The product of the PCA revealed that the chest depth (CHD), body depth (BDD), and udder depth (UDD) traits are the essential body depth dimensions in dairy cattle. A crowning envoy associated with the milk yield capacity was delegated to the UDD trait. However, the UDD is the finest trait for the lactation cow selection program. Presumably, the BDD trait is the prime characteristic for calves and heifer selection schemes.